The logic of feminist standpoint theory for social work research. - Swigonski, Mary E. (Social Work, 1994)
This article presents feminist standpoint theory as an epistemology to move social work research and practice toward a synthesis of relevance and rigor. Feminist standpoint theory provides an alternative approach to knowledge justification and “good science.” The article discusses three assumptions of positivist approaches to science and research and highlights some of the conflicts between those assumptions and the professional commitments of social work. The specific areas of conflict identified include claims of value free scientific activity, subject-object separation, and scientific objectivity. Feminist standpoint theory is an approach to research that is more consonant with the professional values and goals of social work. The theory places the life experiences of marginalized groups at the center of the research project. It then directs the view of the researcher toward the social structures that shape the lives of the group members. The advantages of standpoint theory for social work practice and research are highlighted. Reprinted by permission of the publisher.